Place of action and tasks of women: the nature (φύσις) as a justification of customs (νόμοι) in the Economics, by Xenophon - Mafra, Janaína Silveira (Revista Archai, 2024)
Xenophon was one of the most disregard classical authors of the last century. The discredit that marked his Socratic writings is a consequence of the conclusions reached, at the beginning of the 20th century, by some historians who were looking for a solution to the Socratic Question. According to some commentators, since the origins of this Question, Xenophon’s testimony was subjected to merciless criticism: 1) Xenophon was not a philosopher, but rather a military and politician and 2) Xenophon was committed to defending his master from the accusation of being subversive, representing the established order and traditional values. In harmony with such commentators (L.-A. Dorion, L. Brisson e L. Rossetti), we think that Xenophon is a philosopher whose work has qualities that are intrinsic to it. However, we also think that, if, on the one hand, today the rehabilitation of Xenophon’s Socratic writings is quite advanced, on the other hand, we should not silence any and all problematizations of the content of his philosophy, because such an attempt would be as harmful as that of silencing the philosopher. Based on this consideration, the intention of this paper is to show that - although Xenophon, in the Economics, establishes through the mouth of Ischomachus what is the place of action (χώρα) and what are the tasks or functions (ἔργα) of women within the city, claiming that they must stick to the interior of the house and perform the tasks or functions that inherent to them by nature (φύσει), which customs (νόμοι) confirm - the argument from nature (φύσις) has in this work the rhetorical role of justifying customs (νόμοι), protecting them from critical attacks.